Study the consumer’s purchasing behavior towards the auto ‎sector in Algeria - Lahcene, Attallah (Dirassat Journal Economic Issue, 2016)
The study of consumer purchasing behavior is essential for companies in order to adapt a customer-oriented marketing strategy which aims to ensure the satisfaction of consumer needs and desires and often consumer purchasing behavior is influenced. by cultural, social, personal and psychological factors. The objective of this study is to answer the following question: what are the factors influencing the purchase of a car in Algeria The results of this study confirmed that the purchasing behavior of consumers towards the automotive sector strongly influenced by three main factors: 1) the technical characteristics of the automobile. 2) The competitive advantage of the automobile. 3) Social factors.